The Influence of the Side Rake Angle of the Cut on the Flat Turning Process to Flank Wear of HSS Cutting Tool - Anrinal; Asmara Yanto; Khairun Nizam (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2021)
The purpose of this study is to provide an overview of the effect of the side rake angle in the medium carbon steel flat turning process on the flank wear of the HSS cutting tool. This research was conducted using a PL 1000 lathe, cutting speed (Vc) 24 m/min, cutting depth 0.25 mm, feeding motion 0.26 mm/r, using an HSS cutting tool with side rake angle variations (γo) 120, 180, 250. Flank wear was measured using the Toolmaker Microscope with an accuracy of 0.005 mm, a clearance of 25 mm, and a magnification of 15 times. The results showed that the increase in side rake angle in the medium carbon steel flat lathe process tended to result in an increase in the flank wear of the HSS cutting tool. The large side cutting angle (250) has the highest wear value of 0.55 mm. The lowest wear value occurs at an angle of 120 with a wear of 0.49 mm.